Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4193/rhin20.116
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of New Onset Anosmia During the COVID-19 Pandemic

Abstract: Introduction: Anosmia has not been formally recognised as a symptom of COVID-19 infection. Growing anecdotal evidence suggests increasing incidence of cases of anosmia during the current pandemic, suggesting that COVID-19 may cause olfactory dysfunction. The objective was to characterise patients reporting new onset anosmia during the COVID-19 pandemic Methodology: Design: Survey of 2428 patients reporting new onset anosmia during the COVID-19 pandemic. Setting: Volunteer sample of patients seeking medical adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
297
6
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(342 citation statements)
references
References 14 publications
(15 reference statements)
25
297
6
14
Order By: Relevance
“…Chemosensitive dysfunction is now considered one of the most frequent symptoms in the early stages of coronavirus disease 2019 (Covid-19). [1][2][3][4][5][6][7][8][9][10][11] Objective psychophysical evaluation is challenging because of logistical and safety problems. Consequently, as of 1 July 2020, only six retrospective psychophysical studies have been published, [12][13][14][15][16][17] and only three of them investigate both olfactory and gustatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemosensitive dysfunction is now considered one of the most frequent symptoms in the early stages of coronavirus disease 2019 (Covid-19). [1][2][3][4][5][6][7][8][9][10][11] Objective psychophysical evaluation is challenging because of logistical and safety problems. Consequently, as of 1 July 2020, only six retrospective psychophysical studies have been published, [12][13][14][15][16][17] and only three of them investigate both olfactory and gustatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Viral infections are common causes of olfactory loss, and tran sient loss is likely under-reported. 5 Over the last 2 months, an increase of sudden isolated anosmia incidence, with or without taste loss, was reported. In this study chemosensitive dysfunction appeared in high percentage of the COVID-19 positive patients, 89.23% of patients had smell dysfunction and 83.08 had taste dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reported this gender percentage. [5][6][7][8] Most cases were mild, followed by moderate, then total anosmia and or taste loss. There must recognition of the patient felling to have chemosensitive disorders and the real presence of such dysfunction, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of OD may vary regarding the clinical setting, with rates of total loss of smell as high as 70% in patients with mild COVID-19 form. 2,4,5 The prevalence of OD in moderate-to-critical COVID-19 forms was poorly investigated. Moreover, there is, to date, a paucity of studies prospectively studying the recovery rates of smell sense in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%